Innovative School Leadership : transforming practices - Richards, Gill; Wheatley, Chris (CEO) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Written by school leaders, for school leaders, this book shares the work of ten practising, innovative school leaders. It offers insight into practical school developments that have been researched, trialled and reviewed to demonstrate their success at creating positive change. With each chapter written by experienced school leaders working in a range of contexts, the accounts of the developments they carried out and the research evidence they collected to measure impact are presented accessibly and succinctly. These developments include: Poverty Proofing by breaking down barriers to disadvantage Creating a new holistic approach to appraisal and quality assurance How to design and deliver a new cohesive whole school curriculum Headteacher stress, and how to survive Innovative School Leadership: Transforming Practices is an indispensable resource for all current and aspiring to leaders wanting to provide the best learning environment for their whole school community"--
Includes bibliographical references and index.
Keywords: Educational leadership; Educational innovations